Triatomic catalyst as well as preparation method and application thereof

By using three atomic catalysts, using three transition metal single-atom components as active components, the problem of slow catalytic degradation of pollutants is solved, and more efficient pollutant degradation and photocatalytic performance is achieved.

CN119386911AActive Publication Date: 2025-02-07XIAN UNIV OF TECH

Patent Information

Application Number
CN202411334614.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-07
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Existing single-atom catalysts are unable to satisfy both the adsorption of persulfate (PMS) and contaminants and the subsequent free radical generation process, resulting in a slow rate of catalytic degradation of contaminants.

Method used

A three-atom catalyst is used, which uses three transition metal single-atom components as active components through a complexing agent and uses carbon nitride as a support. The mass fraction of the active components accounts for 0.5 wt.% to 3 wt of the total mass of the catalyst. %.

Benefits of technology

The three-atom catalyst activates PMS faster through synergistic action, promotes the production of living free radicals, significantly improves catalytic performance, improves pollutant degradation efficiency, and enhances the visible light absorption capacity and carrier separation efficiency of photocatalytic technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386911A_ABST
    Figure CN119386911A_ABST
Patent Text Reader

Abstract

The invention discloses a triatomic catalyst, which is characterized in that three transition metal single atoms isolated from each other are confined into units as active components through a complexing agent, carbon nitride is used as a carrier, and the mass fraction of the active components accounts for 0.5-3 wt.% of the total mass of the catalyst. The invention also discloses a preparation method of the triatomic catalyst. The invention also discloses an application of the three-atom catalyst in a photo-Fenton reaction. According to the three-atom catalyst and the preparation method and application thereof disclosed by the invention, a unique configuration (simultaneous close-range adsorption) is provided for adsorption of pollutants and an oxidizing agent. Meanwhile, a photocatalysis technology and an advanced oxidation technology are combined, so that higher visible light absorption capacity and carrier separation efficiency are shown, and PMS or O2 is more easily activated to generate active oxygen species.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new material catalyst synthesis methods, and specifically relates to a three-atom catalyst, and also relates to a preparation method and application of the three-atom catalyst. Background Art

[0003] Traditional wastewater treatment strategies rely on the Fenton process, which uses Fe 2+ / H2O2 system degrades pollutants discharged into water bodies. In this system, Fe 2+ Acting as a catalyst, it activates H2O2 molecules, prompting them to generate highly oxidizing hydroxyl radicals (·OH), which then gradually oxidize and decompose organic pollutants in the water into harmless small molecules, and eventually convert them into carbon dioxide (CO2). However, H2O2 itself has the disadvantages of limited mineralization capacity and easy explosion, which significantly increases the complexity and cost of its transportation and storage.

[0004] In order to overcome these limitations, the scientific community has developed a series of advanced oxidation technologies as alternatives, among which the new persulfate advanced oxidation technology is particularly eye-catching. This technology stands out with its excellent oxidation performance, which activates persulfate to produce sulfate radicals (·SO4 - ). The redox potential of these free radicals is as high as 2.5-3.1V, which is significantly better than the 1.8-2.7V of hydroxyl radicals, showing stronger oxidation ability. In addition, sulfate radicals also have the significant advantages of fast reaction rate, strong environmental adaptability, mild operating conditions and high mineralization efficiency of organic pollutants, opening up a new way for the effective treatment of water pollutants.

[0005] In addition, photocatalysis is a new technology that can effectively utilize solar energy. Photocatalysis technology is clean, pollution-free, and renewable. However, traditional photocatalysts have weak absorption capacity for visible light and low carrier separation efficiency under visible light, which greatly limits the application of photocatalysis technology. Combining photocatalysis technology with Fenton oxidation technology, using the free electrons in the conduction band of semiconductor photocatalysis reactions, persulfate can be activated into SO4 - , and synergistically produce ·OH, ·O2 - It is a more promising new technology to improve the removal capacity of pollutants.

[0006] Single-atom catalysts refer to when the size of surface metal particles is reduced to the scale of a single atom, they can coordinate with atoms on the surface of the carrier to form uniform localized active sites, forming single-atom catalysts. The improvement in the activity of single-atom catalysts is because the reduction in the size of surface metal particles can bring more unsaturated coordination environments, exposing more active sites, thereby promoting the improvement of catalytic performance. However, single atoms also have limitations. A single single-atom site cannot simultaneously satisfy the adsorption of PMS and pollutants and the subsequent free radical generation process, resulting in a slow rate of catalytic degradation of pollutants. Summary of the invention

[0007] The purpose of the present invention is to provide a three-atom catalyst, which solves the problem that the existing single-atom catalyst cannot simultaneously meet the adsorption of PMS and pollutants and the subsequent free radical generation process, resulting in a slow rate of catalytic degradation of pollutants.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned three-atom catalyst.

[0009] The third object of the present invention is to provide the use of the above-mentioned three-atom catalyst in the photo-Fenton reaction.

[0010] The first technical solution adopted by the present invention is: a three-atom catalyst, which uses a complexing agent to form three isolated transition metal single-atom components as active components, uses carbon nitride as a carrier, and the mass fraction of the active components accounts for 0.5wt.% to 3wt.% of the total mass of the catalyst.

[0011] The first technical solution adopted by the present invention is also characterized in that:

[0012] Furthermore, the transition metal single atom is one or more of transition metals Fe, Co, Cu, Ni, and Mn.

[0013] The second technical solution adopted by the present invention is: a method for preparing a three-atom catalyst, which is prepared according to the following steps:

[0014] Step 1: preparing a carbon nitride support by pyrolysis;

[0015] Step 2: preparing a ternary metal single atom catalyst precursor by complexation;

[0016] Step 3: Pyrolysis to obtain the three-atom catalyst.

[0017] The second technical solution adopted by the present invention is also characterized in that:

[0018] Furthermore, step 1 is specifically as follows: weigh 15g to 30g of melamine, transfer it to a crucible, and in an air atmosphere, heat it to 500°C to 550°C at a heating rate of 5°C / min in a muffle furnace, and keep it warm for 3h to 4h to obtain a carbon nitride carrier.

[0019] Furthermore, step 2 is as follows: weigh 2.5 mg to 140 mg of one or more metal salts, add them to 7.5 mL to 10 mL of solvent 1, and dissolve them completely by ultrasound to obtain solution A; at the same time, add 50 μL to 300 μL of a ternary complexing agent to 1 mL to 3 mL of solvent 2, and mix them evenly by ultrasound to obtain solution B; mix solutions A and B evenly, transfer them to an oil bath at 70° C. to 90° C., add 0.1 g to 0.5 g of a carbon nitride carrier, and stir the mixture at a speed of 500 rpm for 30 min to 60 min; centrifuge to obtain a solid product, wash it with ethanol 2 to 3 times, and transfer it to a 60° C. oven for drying for 12 h.

[0020] Furthermore, in step 2, the metal salt precursor is any one or more of chlorides, nitrates or sulfates of transition metals Fe, Co, Cu, Ni, and Mn; solvent 1 is any one or more of acetone, butanone, ethanol, ethylene glycol, isopropanol, and ethyl acetate; solvent 2 is any one or more of acetonitrile, methanol, ethanol, isopropanol, and diisopropyl ether; and the ternary complexing agent is triethanolamine or triethylamine.

[0021] Furthermore, the drying method in step 2 is any one of conventional drying, vacuum drying and freeze drying.

[0022] Furthermore, step 3 is as follows: grind the dried ternary metal single atom cluster catalyst precursor in a mortar for 10 minutes, transfer it to a tubular furnace, increase the temperature to 550°C at a heating rate of 5°C / min under a certain atmosphere, and calcine for 2 hours to obtain the catalyst; the calcination atmosphere is any one of air, nitrogen, and hydrogen, or a mixture of two gases.

[0023] The third technical solution adopted by the present invention is: application of three-atom catalyst in photo-Fenton reaction,

[0024] The third technical solution adopted by the present invention is also characterized in that:

[0025] Furthermore, 50 mL of an organic pollutant solution with a concentration of 5 mg / L to 25 mg / L is used as the raw material liquid, the solvent is water, the amount of catalyst is 5 mg to 20 mg, the mass ratio of the oxidant to the catalyst is 0.5 to 2:1, the reaction is carried out in the visible light range of a xenon lamp light source at room temperature, and the stirring rate is 300 rpm to 800 rpm; the organic pollutant is any one of a dye, an antibiotic, and a phenolic compound, and the oxidant is any one of hydrogen peroxide, permonosulfate PMS, and peroxydisulfate PDS.

[0026] The beneficial effects of the present invention are:

[0027] The three-atom catalyst of the present invention confines three atoms to further maximize its strengths and minimize its weaknesses. The different transition metal single atoms between its active sites will produce a synergistic effect, activate PMS more quickly, and promote the generation of active free radicals, which will further enhance the catalytic performance of the catalyst compared to single-atom catalysts.

[0028] The three-atom catalyst of the present invention provides a unique configuration for the adsorption of pollutants and oxidants. At the same time, the photocatalytic technology is combined with the advanced oxidation technology to show a higher visible light absorption capacity and carrier separation efficiency.

[0029] The three-atom catalyst of the present invention provides a unique catalyst configuration of a confined ternary metal single atom, which not only exhibits a unique adsorption configuration (simultaneous close-range adsorption) for the adsorption of organic pollutants and oxidants in the photo-Fenton reaction, but also has a more negative conduction band energy level, making it easier to activate PMS or O2 to generate active oxygen species. At the same time, the three-atom structure of the catalyst promotes the visible light response of carbon nitride, provides multiple channels for carrier transport, and has better photogenerated carrier separation and transport performance than single atoms. In addition, the preparation method of the present invention is unique, and a ternary complexing agent is used to successfully anchor confined transition metal triatoms on the surface of carbon nitride materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a graph of the degradation efficiency of the single-atom, single-metal triatom, and bimetal triatom catalysts of Example 1 of the present invention under visible light for 90 minutes;

[0031] Figure 2 This is a graph showing the degradation efficiency of three-atom catalysts with different active components under visible light for 90 minutes in Example 2 of the present invention;

[0032] Figure 3 This is a graph of degradation efficiency under different activation conditions in Example 3 of the present invention;

[0033] Figure 4 This is a graph showing the degradation efficiency of the three-atom catalysts with different loading amounts under visible light for 90 minutes according to Example 4 of the present invention;

[0034] Figure 5 This is a 90-min degradation efficiency diagram for different oxidant addition amounts in Example 5 of the present invention;

[0035] Figure 6 This is a 90-min degradation efficiency diagram for different catalyst addition amounts in Example 6 of the present invention;

[0036] Figure 7 This is a graph showing the degradation efficiency of the three-atom catalyst in Example 7 of the present invention under different pollutants.

[0037] Figure 8 The degradation efficiency diagram of the three-atom catalyst with different carriers is prepared by changing the carrier preparation conditions in Example 8 of the present invention.

[0038] Fig. 9 The degradation efficiency diagrams of three-atom catalysts with different precursors were prepared by changing the preparation conditions of the three-atom catalyst precursor according to Example 9 of the present invention. DETAILED DESCRIPTION

[0039] The present invention will be further described below through the accompanying drawings and specific embodiments.

[0040] The present invention provides a three-atom catalyst, wherein three isolated transition metal single-atom component units are used as active components through a complexing agent, and carbon nitride is used as a carrier, and the mass fraction of the active components accounts for 0.5wt.% to 3wt.% of the total mass of the catalyst; the single-atom active component is one or more of transition metals Fe, Co, Cu, Ni, and Mn, and the carrier is carbon nitride. The carbon nitride carrier is prepared by a pyrolysis method, and organic matter is thermally decomposed to form a carrier precursor; a ternary metal single-atom cluster precursor is prepared by a complexing method, and a metal ion is connected to the carrier by a ternary complexing agent to form a ternary metal single-atom cluster catalyst precursor; finally, the three-atom catalyst is prepared by a pyrolysis method, and the ternary metal single-atom cluster catalyst precursor is ground and calcined to prepare the three-atom catalyst.

[0041] The three-atom catalyst of the present invention confines three atoms within a certain range, further enhancing the advantages and avoiding the disadvantages. The different transition metal single atoms between its active sites will produce a synergistic effect, activate PMS more quickly, and promote the generation of active free radicals. Compared with the single-atom catalyst, the catalytic performance of the catalyst will be further improved.

[0042] The present invention also provides a method for preparing a three-atom catalyst, which is specifically prepared according to the following steps:

[0043] Step 1: Prepare the carbon nitride carrier by pyrolysis. Weigh 15g to 30g of melamine, transfer it to a crucible, and heat it to 500℃ to 550℃ in a muffle furnace at a heating rate of 5℃ / min under air atmosphere, and keep it warm for 3h to 4h to obtain the carbon nitride carrier;

[0044] Step 2: Prepare the ternary metal single atom cluster catalyst precursor by complexation. Weigh 2.5mg to 140mg of one or two metal salts, add them to 7.5mL to 10mL of solvent 1, and dissolve them completely by ultrasound to obtain solution A; at the same time, add 50μL to 300μL of ternary complexing agent to 1mL to 3mL of solvent 2, and mix them evenly by ultrasound to obtain solution B; mix solutions A and B evenly, transfer to an oil bath at 70℃ to 90℃, add 0.1g to 0.5g of carbon nitride carrier, and stir the mixture at a speed of 500rpm for 30min to 60min; centrifuge to obtain a solid product, wash it with ethanol 2 to 3 times, and transfer it to a 60℃ oven for drying for 12h.

[0045] In step 2, the metal salt precursor is any one of chloride, nitrate, and sulfate, solvent 1 is any one or more of acetone, butanone, ethanol, ethylene glycol, isopropanol, and ethyl acetate, solvent 2 is any one or more of acetonitrile, methanol, ethanol, isopropanol, and diisopropyl ether, and the ternary complexing agent is any one of triethanolamine and triethylamine.

[0046] Step 3: Pyrolysis to obtain a three-atom catalyst. Grind the dried ternary metal single atom cluster catalyst precursor in a mortar for 10 minutes, transfer it to a tube furnace, heat it to 500°C to 600°C at a heating rate of 5°C / min under a certain atmosphere, and calcine it for 1h to 3h to obtain the catalyst;

[0047] In step 3, the drying method is any one of conventional drying, vacuum drying, and freeze drying; the roasting atmosphere is any one of air, nitrogen, and hydrogen, or a mixture of two gases.

[0048] The method for photo-Fenton degradation of organic pollutants using the three-atom catalyst prepared by the present invention adopts 50 mL of an organic pollutant solution with a concentration of 5 mg / L to 25 mg / L as a raw material liquid, and the solvent is water; the amount of the catalyst is 5 mg to 20 mg; the mass ratio of the oxidant to the catalyst is 0.5 to 2:1, and the reaction is carried out in the visible light range of a xenon lamp light source at room temperature, and the stirring rate is 300 rpm to 800 rpm.

[0049] The organic pollutant can be any one of dyes, antibiotics, and phenolic compounds.

[0050] The oxidant is any one of hydrogen peroxide, peroxymonosulfate (PMS) and peroxydisulfate (PDS).

[0051] The preparation of the catalyst of the present invention and its performance are further described below through specific examples.

[0052] Example 1

[0053] This example prepares three-atom catalysts with different ratios of metal atoms:

[0054] First, 15 g of melamine was weighed and transferred to a crucible. The temperature was increased to 500° C. at a heating rate of 5° C. / min in a muffle furnace under air atmosphere and kept at this temperature for 3 h to obtain a carbon nitride carrier.

[0055] Then, 3.5 mg of cobalt nitrate hexahydrate and 2.6 mg of ferric nitrate nonahydrate, 1.8 mg of cobalt nitrate hexahydrate and 5.3 mg of ferric nitrate nonahydrate, 7.8 mg of ferric nitrate nonahydrate, 5.2 mg of cobalt nitrate hexahydrate, 2.6 mg of ferric nitrate nonahydrate, and 1.7 mg of cobalt nitrate hexahydrate were weighed and added to 7.5 mL of acetone solution, and all of them were dissolved by ultrasound to obtain solution A; at the same time, 200 μL of triethanolamine was added to 1 mL of acetonitrile solution, and the mixture was mixed by ultrasound to obtain solution B; solutions A and B were mixed evenly, transferred to an oil bath at 70°C, 0.1 g of carbon nitride carrier was added, and the mixture was stirred at a speed of 500 rpm for 40 min; the solid product was obtained by centrifugation, washed with ethanol 3 times, and transferred to a 60°C oven for drying for 12 h.

[0056] Finally, the dried ternary metal single atom cluster catalyst precursor and single atom catalyst precursor were ground in a mortar for 10 min, transferred to a tube furnace, heated to 550 °C at a heating rate of 5 °C / min under a nitrogen atmosphere, and calcined for 2 h to obtain a three-atom catalyst and a single atom catalyst with a theoretical active component accounting for 1% of the catalyst, denoted as Fe1Co2-CN-1%, Fe2Co1-CN-1%, Fe3-CN-1%, Co3-CN-1%, Fe1-CN-1%, Co1-CN-1%. The ICP test showed that Fe1Co2- The actual loading amounts of single iron atoms and single cobalt atoms in the CN-1% and Fe2Co1-CN-1% tri-atom catalysts are 0.29% and 0.59%, 0.63% and 0.25% respectively; the actual loading amount of iron atoms in the Fe3-CN-1% tri-atom catalyst is 0.98%; the actual loading amount of single cobalt atoms in the Co3-CN-1% tri-atom catalyst is 0.96%; the actual loading amount of iron atoms in the Fe1-CN-1% single atom catalyst is 0.96%; and the actual loading amount of iron atoms in the Co1-CN-1% single atom catalyst is 0.93%.

[0057] 10 mg of each of the above three-atom catalyst and the single-atom catalyst were added to 50 mL of a 15 mg / L phenol solution, and stirred at 500 rpm in the dark for 30 min. At this time, the absorbance of the phenol solution was detected by UV-visible spectroscopy, recorded as C0, and the time was recorded as t0. 10 mg of potassium permonosulfate was added, and the mixture was continuously stirred under visible light (400-760 nm) of a xenon lamp source. Samples were taken for analysis and detection every 15 min, and the absorbance of the solution was recorded as C, and the time was recorded as t, to obtain a degradation efficiency graph.

[0058] like Figure 1 As shown in the figure, after 90 min, the Fe1Co2-CN-1% catalyst has the best catalytic degradation performance for phenol, with a degradation rate of 100%. Compared with the carrier carbon nitride CN, the oxidation degradation activity is greatly improved by using transition metal single atom active components. Therefore, the transition metal single atom is the active center. At the same time, the catalytic performance of the three-atom catalyst is significantly higher than that of the single atom catalyst, and the catalytic performance of the three-atom catalyst of two metal atoms is better than that of the three-atom catalyst of one metal atom. This may be due to the synergistic effect between the three atoms in the confinement, and the change of geometry and electronic structure. The two-metal three-atom catalyst can adsorb and activate PMS while adsorbing phenol, further improving the catalytic performance of the catalyst.

[0059] Example 2

[0060] This example prepares three-atom catalysts with different active components:

[0061] First, 15 g of melamine was weighed and transferred to a crucible. The temperature was increased to 500° C. at a heating rate of 5° C. / min in a muffle furnace under air atmosphere and kept at this temperature for 3 h to obtain a carbon nitride carrier.

[0062] Then, 3.5 mg of cobalt nitrate hexahydrate and 2.6 mg of ferric nitrate nonahydrate were weighed, added to 7.5 mL of acetone solution, and dissolved completely by ultrasound to obtain solution A; at the same time, 200 μL of triethanolamine was added to 1 mL of acetonitrile solution, and mixed evenly by ultrasound to obtain solution B; solutions A and B were mixed evenly, transferred to an oil bath at 70°C, 0.1 g of carbon nitride carrier was added, and the mixture was stirred at 500 rpm for 40 min; a solid product was obtained by centrifugation, washed with ethanol three times, and transferred to a 60°C oven for drying for 12 h.

[0063] Finally, the dried ternary metal single atom cluster catalyst precursor was ground in a mortar for 10 minutes, transferred to a tubular furnace, and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere and calcined for 2 hours to obtain a three-atom catalyst in which the theoretical active component accounted for 1% of the catalyst. The actual loading amounts of iron single atoms and cobalt single atoms were 0.29% and 0.59% by ICP testing, respectively, and were recorded as Fe1Co2-CN-1%.

[0064] This embodiment also uses different active transition metal precursors to replace ferric nitrate nonahydrate and cobalt nitrate hexahydrate to prepare a three-atom catalyst, and finally obtains a three-atom catalyst in which the theoretical metal accounts for 1% of the total mass of the catalyst, and the actual loading amount of the three atoms is 0.29% and 0.59% respectively. The different catalysts are: Fe1Cu2-CN-1%, Fe1Ni2-CN-1%, and Fe1Mn2-CN-1%.

[0065] Take 10 mg of each of the above three-atom catalysts and add them to 50 mL of 15 mg / L phenol solution. Stir for 30 min in the dark at a speed of 500 rpm. At this time, the absorbance of the phenol solution is detected by ultraviolet visible spectrum, recorded as C0, and the time is recorded as t0. Add 10 mg of potassium permonosulfate, continue stirring under visible light (400-760 nm) of a xenon lamp light source, take samples for analysis and detection every 15 min, record the absorbance of the solution as C, and the time as t, and obtain a catalytic degradation efficiency graph.

[0066] like Figure 2 As shown, after 90 minutes, different catalysts were used to degrade phenol solution. The iron-cobalt triatom catalyst had the best degradation performance with a degradation rate of 100%, which was significantly better than the other two metal combinations. This may be because the triatom catalyst formed by the combination of iron atoms and cobalt atoms is more conducive to the adsorption of phenol and activation of PMS, producing a better synergistic effect.

[0067] Example 3

[0068] 10 mg of Fe1Co2-CN-1% prepared in Example 1 was added to 50 mL of 15 mg / L phenol solution, and stirred at 500 rpm in the dark for 30 min. The absorbance of the phenol solution was detected by UV-visible spectroscopy, recorded as C0, and the time was recorded as t0. Three groups of phenol degradation experiments were performed, including only adding 10 mg of potassium permonosulfate, only adding light, and potassium permonosulfate and light synergistically. Stirring was continued, and samples were taken for analysis and detection every 15 min. The absorbance of the solution was recorded as C, and the time was recorded as t to obtain a catalytic degradation graph.

[0069] like Figure 3 As shown, after 90 minutes, when potassium permonosulfate and light were added at the same time, Fe1Co2-CN-1% had a significant effect on phenol degradation, and the degradation efficiency reached 100%. At the same time, the catalytic performance of Fe1Co2-CN-1% was about 95% higher than that of only adding visible light and only adding PMS, which further illustrates that in this catalytic system, visible light and PMS have a synergistic effect.

[0070] Example 4

[0071] This example prepares three-atom catalysts with different loading amounts:

[0072] First, 15 g of melamine was weighed and transferred to a crucible. The temperature was increased to 500° C. at a heating rate of 5° C. / min in a muffle furnace under air atmosphere and kept at this temperature for 3 h to obtain a carbon nitride carrier.

[0073] Then, 1.7 mg of cobalt nitrate hexahydrate and 1.3 mg of ferric nitrate nonahydrate, 7.0 mg of cobalt nitrate hexahydrate and 5.2 mg of ferric nitrate nonahydrate, 11.9 mg of cobalt nitrate hexahydrate and 8.7 mg of ferric nitrate nonahydrate were weighed, added to 7.5 mL of acetone solution, and dissolved completely by ultrasound to obtain solution A; at the same time, 200 μL of triethanolamine was added to 1 mL of acetonitrile solution and mixed evenly by ultrasound to obtain solution B; solutions A and B were mixed evenly, transferred to an oil bath at 70°C, 0.1 g of carbon nitride carrier was added, and the mixture was stirred at a speed of 500 rpm for 40 min; a solid product was obtained by centrifugation, washed with ethanol 3 times, and transferred to a 60°C oven for drying for 12 h.

[0074] Finally, the dried ternary metal single atom cluster catalyst precursor was ground in a mortar for 10 minutes, transferred to a tubular furnace, heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcined for 2 hours to obtain three-atom catalysts in which the theoretical active components accounted for 0.5%, 2%, and 3% of the catalyst. ICP tests showed that the actual loading amounts of iron single atoms and cobalt single atoms were 0.14%, 0.52%, 0.91% and 0.32%, 1.31%, 1.92%, respectively, recorded as Fe1Co2-CN-0.5%, Fe1Co2-CN-2%, and Fe1Co2-CN-3%, respectively.

[0075] Take 10 mg of each of the three atom catalysts above and add them to 50 mL of 15 mg / L phenol solution. Stir at 500 rpm in the dark for 30 min. The absorbance of the phenol solution is detected by UV-visible spectroscopy and recorded as C0, and the time is recorded as t0. Add 10 mg of potassium permonosulfate and continue stirring under visible light (400-760 nm) of a xenon lamp. Take samples for analysis every 15 min. The absorbance of the solution is recorded as C and the time is recorded as t. After 90 min, if Figure 4 As shown, the Fe1Co2-CN-1% catalyst has the best catalytic degradation performance for phenol, and the degradation rate is 100%.

[0076] Example 5

[0077] Take 10 mg of the Fe1Co2-CN-1% catalyst prepared in three groups of Example 1, add them to 50 mL of 15 mg / L phenol solution, stir at 500 rpm in the dark for 30 min, then the absorbance of the phenol solution is detected by UV-visible spectrum, recorded as C0, and the time is recorded as t0. Add 5 mg, 10 mg, 15 mg, and 20 mg of potassium permonosulfate respectively, continue stirring under the visible light (400-760 nm) of a xenon lamp, take samples for analysis and detection every 15 min, record the absorbance of the solution as C, and the time as t. After 90 min, if Figure 5As shown, the degradation rates of phenol in the samples with 5 mg, 10 mg, 15 mg and 20 mg of potassium permonosulfate were 89.74%, 100%, 100% and 100%, respectively. Considering the economic benefits, 10 mg of potassium permonosulfate was the optimal addition amount.

[0078] Example 6

[0079] Take 5mg, 10mg, 15mg, and 20mg of the Fe1Co2-CN-1% catalyst prepared in Example 1, add it to 50mL of 15mg / L phenol solution, stir it at 500rpm in the dark for 30min, then the absorbance of the phenol solution is detected by UV-visible spectrum, recorded as C0, and the time is recorded as t0. Add 10mg of potassium permonosulfate, continue stirring under the visible light (400-760nm) of xenon lamp, take samples for analysis every 15min, record the absorbance of the solution as C, and the time as t. After 90min, if Figure 6 As shown in the figure, when the addition amount is 10 mg, phenol is first and completely degraded within 90 min. Taking all factors into consideration, the addition amount of catalyst is 10 mg, which is the optimal addition amount.

[0080] Example 7

[0081] Take 10 mg of the Fe1Co2-CN-1% catalyst prepared in three groups of Example 1, add them to 50 mL of 15 mg / L tetracycline solution, rhodamine B solution, and bisphenol A solution, respectively, and stir them at 500 rpm in the dark for 30 minutes. At this time, the absorbance of each solution is detected by ultraviolet visible spectrum, recorded as C0, and the time is recorded as t0. Add 10 mg of potassium permonosulfate respectively, continue stirring under the visible light (400-760 nm) of a xenon lamp light source, take samples for analysis and detection every 15 minutes, record the absorbance of the solution as C, and the time as t. After 90 minutes, if Figure 7 As shown, the catalytic degradation efficiency of Fe1Co2-CN-1% catalyst for various pollutants can reach 100% within 90 minutes. Taking all factors into consideration, Fe1Co2-CN-1% catalyst has universal applicability in degrading pollutants.

[0082] Example 8

[0083] This example changes the carrier preparation conditions to prepare three-atom catalysts with different carriers:

[0084] First, 20 g of melamine and 30 g of melamine were weighed respectively, transferred to a crucible, and heated to 520°C and 550°C, respectively, at a heating rate of 5°C / min in a muffle furnace under an air atmosphere, and kept warm for 3.5 h and 4 h, respectively, to obtain carbon nitride carriers CN1 and CN2.

[0085] Then weigh 3.5 mg of cobalt nitrate hexahydrate and 2.6 mg of ferric nitrate nonahydrate, add them to 7.5 mL of acetone solution, and sonicate to dissolve them completely to obtain solution A; at the same time, add 200 μL of triethanolamine to 1 mL of acetonitrile solution, and sonicate to mix them evenly to obtain solution B; mix solutions A and B evenly, transfer to a 70°C oil bath, add 0.1 g CN1 and 0.1 g CN2 carbon nitride carriers respectively, and stir the mixture at 500 rpm for 30 min; centrifuge to obtain a solid product, wash it with ethanol three times, and transfer it to a 60°C oven for drying for 12 h.

[0086] Finally, the dried ternary metal single atom cluster catalyst precursor was ground in a mortar for 10 minutes, transferred to a tubular furnace, and heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere and calcined for 2 hours to obtain a three-atom catalyst in which the theoretical active component accounted for 1% of the catalyst. ICP testing showed that the actual loading amounts of iron single atoms and cobalt single atoms were 0.26% and 0.25% and 0.54% and 0.55%, respectively, recorded as Fe1Co2-CN1-1% and Fe1Co2-CN2-1%, respectively.

[0087] Take 5 mg of each of the above three-atom catalyst and Fe1Co2-CN-1% prepared in Example 1 and add them to 50 mL of phenol solution with a concentration of 5 mg / L. Stir for 30 min in the dark at a speed of 300 rpm. At this time, the absorbance of the phenol solution is detected by ultraviolet visible spectrum, recorded as C0, and the time is recorded as t0. Add 10 mg of potassium permonosulfate, continue stirring under the visible light (400-760 nm) of a xenon lamp light source, take samples for analysis and detection every 15 min, record the absorbance of the solution as C, and the time as t. Figure 8 As shown, the degradation efficiency of the prepared three-atom catalysts reached 100% within 90 minutes, showing excellent catalytic degradation performance, and there was no obvious difference in the degradation trend of the different three-atom catalysts prepared during the degradation of phenol solution, which shows that in the process of preparing the three-atom catalyst, when carriers with different preparation temperature conditions are added, the three-atom catalyst still has excellent and similar catalytic degradation performance, further proving that different carriers will not have a significant effect on the formation of stable and reliable active centers of transition metal atoms in the three-atom catalyst.

[0088] Example 9

[0089] This example changes the preparation conditions of the three-atom catalyst precursor to prepare three-atom catalysts with different precursors:

[0090] First, 15 g of melamine was weighed and transferred to a crucible. The temperature was increased to 500° C. at a heating rate of 5° C. / min in a muffle furnace under air atmosphere and kept at this temperature for 3 h to obtain a carbon nitride carrier.

[0091] Then, two portions of 3.5 mg of cobalt nitrate hexahydrate and 2.6 mg of ferric nitrate nonahydrate were weighed and added to 9 mL and 10 mL of acetone solutions, respectively, and dissolved completely by ultrasound to obtain solutions A1 and A2; at the same time, 150 μL and 300 μL of triethanolamine were added to 2 mL and 3 mL of acetonitrile solutions, respectively, and mixed evenly by ultrasound to obtain solutions B1 and B2; solutions A1 and B1, A2 and B2 were mixed evenly, transferred to oil baths at 80°C and 90°C, respectively, 0.1 g of carbon nitride carrier was added, and the mixture was stirred at 500 rpm for 50 min and 60 min, respectively; the solid product was obtained by centrifugation, washed with ethanol 3 times, and transferred to an oven at 60°C for drying for 12 h.

[0092] Finally, the dried ternary metal single atom cluster catalyst precursor was ground in a mortar for 10 minutes, transferred to a tubular furnace, heated to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and calcined for 2 hours to obtain a three-atom catalyst in which the theoretical active component accounted for 1% of the catalyst. ICP testing showed that the actual loading amounts of iron single atoms and cobalt single atoms were 0.27% and 0.29% and 0.57% and 0.54%, respectively, recorded as Fe1Co2-CN-1%-1 and Fe1Co2-CN-1%-2.

[0093] Take 20 mg of each of the above three-atom catalysts and add them to 50 mL of 25 mg / L phenol solution. Stir at 800 rpm in the dark for 30 minutes. The absorbance of the phenol solution is detected by UV-visible spectroscopy and recorded as C0, and the time is recorded as t0. Add 10 mg of potassium permonosulfate and continue stirring under visible light (400-760 nm) of a xenon lamp. Take samples for analysis every 15 minutes. The absorbance of the solution is recorded as C and the time is t. Fig. 9 As shown, the catalytic degradation efficiency of the three-atom catalysts prepared under different three-atom catalyst precursor preparation conditions reached 100%, which indicates that the three-atom catalyst precursors prepared under different mass solvents have no effect on the final catalytic degradation performance of the three-atom catalyst.

[0094] In combination with Example 8 and Example 9, the three-atom catalysts prepared under different preparation conditions showed excellent catalytic degradation performance for phenol solutions of different concentrations. It also showed that the three-atom catalysts showed good preparation stability under different preparation conditions.

[0095] A three-atom catalyst of the present invention is a catalyst in which one or more transition metal single atoms are grouped in three to form active sites confined on the surface of a carbon nitride carrier through a unique preparation method. The catalyst metals of the present invention are all dispersed on the surface of the carrier, with strong synergistic ability and high intrinsic activity. It is applied to the degradation of organic pollutants by photo-Fenton reaction, and has obtained excellent catalytic activity and exhibits excellent universality, which can reduce environmental pollution and production and application costs.

Claims

1. A three-atom catalyst, characterized in that: The three-atom catalyst uses a complexing agent to form three isolated transition metal single-atom components as active components, uses carbon nitride as a carrier, and the mass fraction of the active components accounts for 0.5wt.% to 3wt.% of the total mass of the catalyst.

2. The three-atom catalyst according to claim 1, characterized in that: The transition metal single atom is one or more of transition metals Fe, Co, Cu, Ni, and Mn.

3. A method for preparing a three-atom catalyst, characterized in that: Prepare according to the following steps: Step 1: preparing a carbon nitride support by pyrolysis; Step 2: preparing a ternary metal single atom catalyst precursor by complexation; Step 3: Pyrolysis to obtain the three-atom catalyst.

4. The method for preparing a three-atom catalyst according to claim 3, characterized in that: The step 1 is specifically as follows: 15 g to 30 g of melamine is weighed and transferred to a crucible, and in an air atmosphere, the temperature is increased to 500° C. to 550° C. at a heating rate of 5° C. / min in a muffle furnace, and the temperature is kept for 3 h to 4 h to obtain a carbon nitride carrier.

5. The method for preparing a three-atom catalyst according to claim 3, characterized in that: The step 2 is specifically as follows: weigh 2.5 mg to 140 mg of one or more metal salts, add them to 7.5 mL to 10 mL of solvent 1, and ultrasonically dissolve them completely to obtain solution A; at the same time, add 50 μL to 300 μL of a ternary complexing agent to 1 mL to 3 mL of solvent 2, and ultrasonically mix them evenly to obtain solution B; mix solutions A and B evenly, transfer them to an oil bath at 70° C. to 90° C., add 0.1 g to 0.5 g of a carbon nitride carrier, and stir the mixture at a speed of 500 rpm for 30 min to 60 min; centrifuge to obtain a solid product, wash it with ethanol 2 to 3 times, and transfer it to a 60° C. oven for drying for 12 hours.

6. The method for preparing a three-atom catalyst according to claim 5, characterized in that: In step 2, the metal salt precursor is any one or more of chlorides, nitrates or sulfates of transition metals Fe, Co, Cu, Ni and Mn; solvent 1 is any one or more of acetone, butanone, ethanol, ethylene glycol, isopropanol and ethyl acetate; solvent 2 is any one or more of acetonitrile, methanol, ethanol, isopropanol and diisopropyl ether; and the ternary complexing agent is triethanolamine or triethylamine.

7. The method for preparing a three-atom catalyst according to claim 5, characterized in that: The drying method in step 2 is any one of conventional drying, vacuum drying and freeze drying.

8. The method for preparing a three-atom catalyst according to claim 3, characterized in that: The specific steps of step 3 are as follows: the dried ternary metal single atom cluster catalyst precursor is ground in a mortar for 10 minutes, transferred to a tubular furnace, heated to 550°C at a heating rate of 5°C / min under a certain atmosphere, and calcined for 2 hours to obtain the catalyst; the calcination atmosphere is any one of air, nitrogen, and hydrogen, or a mixture of two gases.

9. Use of the three-atom catalyst according to any one of claims 1 to 8 in a photo-Fenton reaction.

10. The use of the three-atom catalyst in the photo-Fenton reaction according to claim 9, characterized in that: 50 mL of an organic pollutant solution with a concentration of 5 mg / L to 25 mg / L is used as a raw material liquid, the solvent is water, the amount of the catalyst is 5 mg to 20 mg, the mass ratio of the oxidant to the catalyst is 0.5 to 2:1, the reaction is carried out in the visible light range of a xenon lamp light source at room temperature, and the stirring rate is 300 rpm to 800 rpm; the organic pollutant is any one of a dye, an antibiotic, and a phenolic compound, and the oxidant is any one of hydrogen peroxide, peroxymonosulfate PMS, and peroxydisulfate PDS.

Citation Information

Patent Citations

  • Transition metal monatomic active catalyst as well as preparation method and application thereof

    CN113600170A

  • Monatomic catalyst for thermal desorption of soil polluted by organic matter and preparation method of monatomic catalyst

    CN113877597A

  • Transition metal polyatomic catalyst on N-doped carbon substrate

    CN117246994A

  • Carbon nitride catalyst, preparation method thereof and efficient pollutant degradation method

    CN117563643A

  • Single-atom catalyst for activation of persulfate to generate pure singlet oxygen as well as preparation method and application thereof

    US20220315425A1

Cited By

  • Porous tubular graphite phase carbon nitride, photocatalyst and preparation method and application of porous tubular graphite phase carbon nitride

    CN120423502A